2019
DOI: 10.1016/j.bjorl.2017.10.014
|View full text |Cite
|
Sign up to set email alerts
|

Nasal patency and otorhinolaryngologic-orofacial features in children

Abstract: Nasal patency was lower in children with restless sleep, rhinitis signs and symptoms, hard palate width reduced and with changes in mastication, deglutition and speech functions. It is also emphasized that most of the children presented signs and symptom of allergic rhinitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 42 publications
1
11
0
3
Order By: Relevance
“…Teachers reported that people who breathe through the mouth may suffer from tiredness (Q2), observed by 85.3% of teachers in the pre-program questionnaire and by 96.7% in the post-questionnaire. It is known that mouth breathing can cause daytime fatigue, due to the altered sleep pattern quality, and this tiredness may be related to poor school performance (8,20) . After the importance of understanding the relationship between tiredness and learning ability in mouth breathers was understood, it was decided to discuss this particular topic in the Speech Therapy Program.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Teachers reported that people who breathe through the mouth may suffer from tiredness (Q2), observed by 85.3% of teachers in the pre-program questionnaire and by 96.7% in the post-questionnaire. It is known that mouth breathing can cause daytime fatigue, due to the altered sleep pattern quality, and this tiredness may be related to poor school performance (8,20) . After the importance of understanding the relationship between tiredness and learning ability in mouth breathers was understood, it was decided to discuss this particular topic in the Speech Therapy Program.…”
Section: Discussionmentioning
confidence: 99%
“…On the subject of difficulties eating (Q3), 71.3% of teachers answered, in the pre-program questionnaire, that mouth breathing may be related to dietary problems, however in the post questionnaire this number increased to 96, 7%. Studies (20,21) show that mouth breathers may have difficulties in chewing with reduced masticatory speed, function disorder and poorer performance of the masseter muscle. Mouth breathers can also suffer from changes in swallowing giving rise to difficulties in swallowing solid foods (15) .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Um estudo que buscou comparar a potência nasal e características otorrinolaringológicas e orofaciais em crianças, identificou redução das vias aéreas superiores em crianças com sinais e sintomas de rinite, redução da largura do palato duro, alte-rações nas funções de mastigação, deglutição, fala e principalmente em crianças com sono agitado 7 .…”
Section: Introductionunclassified